Penyalahgunaan Gedung Konsulat Jenderal Di Negara Penerima, Perspektif Konvensi Wina 1963 - Samuel Silvester Retraubun; Arman Anwar; Josina Augustina Yvonne Wattimena (PATTIMURA Law Study Review, 2023)
ABSTRACT: The Consulate General building is a facility for the sending country in carrying out the duties and functions of consular relations with the receiving country. Purposes of the Research: Studying and knowing the Functions of the Consulate General Building in the Receiving Country, Perspective of the 1963 Vienna Convention, To study and find out the Legal Consequences of Misuse of the Consulate General Building and Its Impact on Diplomatic Relations of the Two Countries. Methods of the Research: Normative juridical research method, namely obtaining data from the library in the form of documents, books, magazines and other literature related to writing. Results of the Research: The results of the study show that in the perspective of the 1963 Vienna Convention, the rights and obligations of the sending and receiving countries have been regulated in a balanced manner towards the implementation of the functions of the consulate building in order to expand cooperation in consular relations. On the one hand, the sending country has special rights and immunity to its consulate building and is obliged to function it according to its designation by respecting the national law of the receiving country.